Service Quality Muthawif dan Promosi terhadap Kepuasan Konsumen pada Perusahaan Tour dan Travel - Risnanamawati Risnanamawati; Erry Sunarya; Dicky Jhoansyah (IPM2KPE, 2022)
The purpose of this study was to measure the effect of service quality and promotion on consumer satisfaction in Tour & Travel companies. This research method is descriptive quantitative. The type of sampling used is random sampling by distributing 79 questionnaires to consumers. The analysis technique used is multiple linear regression analysis, including the coefficient of determination test, multiple correlation coefficient and simultaneous test (F test). The results of the test of the coefficient of determination seen from the value (Adjusted R2) of 0.151 can be interpreted that the effect of service quality and promotion on consumer satisfaction is 17.2% with 82.8% influenced by other factors not described in this study. Based on the F test the probability value of sig. 0.001 < 0.1, which means that together the value of Service Quality (X1) and Promotion (X2) significantly affect Consumer Satisfaction (Y). In conclusion, the variable service quality (service quality) and promotion have a significant effect simultaneously (simultaneously) on consumer satisfaction. Keywords: Consumer Satisfaction, Service Quality, Promotion